The "Planning Approach" in Public Economy - Neal, Alfred C. (Quarterly Journal of Economics, 1940)
I. Introduction. Scope of the discussion, 246.— II. The meaning of "collective demand/" 247.— III. Rational consumers' choice requires knowledge of terms on which alternatives are offered, 248.— Compulsory payment introduces an arbitrary element, 249.— Minimum requirement for maximizing consumers' satisfactions and minimizing their sacrifices, 249.— Voting on projects and revenue plans, 249.— Difficulty of defining "purpose, " 250.— The problem of "ceteris paribus" 251.— Special difficulties in mixed systems, 251.— IV. Democracy no solution, 252.— Reversing a line of expenditure, 252.— Possibility of government's performing any function not denied, 253.